An integrated approach to detect the structural setting of South Dyiur area, Central Western Desert, Egypt, via potential field data. (2nd October 2022) - Tarek, Yara; Sobhy helaly, Ahmad; El-Khafeef, A. A; Khalifa, Khalid; ElSawy, Marwa; Abuhagaza, Abeer A.
Abstract: The South Diyur exploration block of nearly 38, 000 sq. km is located in the Farafra Oasis region in Egypt's Western Desert. The North West-South East (NW-SE) trend is the regional structural surface features in the South Diyur District. The Bouguer gravity and magnetic data have been analyzed to provide new information about the tectonic setting and subsurface structures of the study area. The advanced filtering techniques were used to map structural as well as varying depths of the study area. The total intensity aeromagnetic map was first corrected by the application of the reduction to the pole technique (RTP). Then, the fast Fourier transform is applied on the gravity and magnetic maps to show the regional and residual sources and their depths, using the radial averaged power spectrum curve which divided into two segments; according to the slope, the maximum depth is 4, 000 m that probably reflects the deep sources at this place. And the shallow sources (near-surface geological structures) showed depth of 600 m. The structure of the basement that influences the sedimentary cover thickness and the region's hydrocarbon potentiality is interpreted as uplifts and basins resulted from parallel fault groups. It is found that there are strike slip faults trending NW-SE, regional faults divided the area into many blocks forming grabbens "Misawage graben and Dirrut basin" and horsts "Bahariya-Cairo uplift, " and the residual faults have many trends but the general trend from the rose diagram is west north west-east south east.